PERANAN ASEAN COORDINATING CENTRE FOR HUMANITARIAN ASSISTANCE ON DISASTER MANAGEMENT (AHA CENTRE) DALAM PENANGGULANGAN BENCANA ALAM DI ASIA TENGGARA MELALUI ASEAN AGREEMENT DISASTER MANAGEMENT AND EMERGENCY RESPONSE 2005 (AADMER - Sonya Basamida Marbun (BELLI AC PACIS, 2020)
This article aims to identify and analyze the role of the AHA Centre and the effectiveness of the AHA Centre in overcoming natural disasters in the Southeast Asia region based on AADMER 2005. This article uses prescriptive method with primary and secondary legal resources which are collected through library study method and analyzed by deduction method. Based on the study, the author concludes that the AHA Centre has important roles in Southeast Asia as it is the only body that has functions to overcome natural disasters since there is no comprehensive international law about natural disasters management in universal. The author also concludes that the AHA Centre is effective by analyzing with the international organization effectiveness theory by Fiermann and Bauer.